Kan naturkundskab bane vej for religion? Introduktion til Ludvig Feilbergs psykologi og Levelære - Hansen, Knud; Hartyani, Margit (Dansk Teologisk Tidsskrift, 2012)
The topic of this article is the psychology and teaching of the Danish psychologist, philosopher and poet Ludvig Feilberg (1849- 1912). Feilberg described how, in the human body and mind, two basically different kinds of movement act as forces in opposite directions. He conjectured that these two kinds of forces give rise to two modes of consciousness (nonreflexive and reflexive consciousness). By appropriate use of the basic functions of consciousness we may facilitate its ability to organize itself, thereby making psychological and mental development possible by transformations of the mind. Feilberg experienced that nature is able to open our mind to infinity and eternity. In this, and in other ways, nature may lead us towards or into religion. In view of present-day science it is possible to explain many of Feilberg´s observations, which renders his psychology more readily applicable. Key words: Spontaneity – creation – re-creation – vitalization – organisation – transformation – reflection – life – nature – religion.